2003
DOI: 10.1007/s00213-003-1661-1
|View full text |Cite
|
Sign up to set email alerts
|

GABAA/α1 receptor agonists and antagonists: effects on species-typical and heightened aggressive behavior after alcohol self-administration in mice

Abstract: Benzodiazepine antagonists, particularly those acting preferentially at GABAA/alpha1 subunit-containing receptors, decrease alcohol-heightened and species-typical aggressive behavior, but are ineffective in attenuating the sedative effects of alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 53 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…The GABA A α 1 subunit may mediate aggressive behavior When administered in combination with midazolam, the GABA A /α 1 -preferring β-carboline, β-CCt, systematically and robustly decreased midazolam-heightened aggressive behavior, extending similar effects found in the mouse, in which β-CCt was 5 times more potent than flumazenil in antagonizing alcohol-heightened aggressive behavior (de Almeida et al 2004). Another β-carboline, 3-PBC, antagonized aggressive behavior at even lower doses than β-CCt.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The GABA A α 1 subunit may mediate aggressive behavior When administered in combination with midazolam, the GABA A /α 1 -preferring β-carboline, β-CCt, systematically and robustly decreased midazolam-heightened aggressive behavior, extending similar effects found in the mouse, in which β-CCt was 5 times more potent than flumazenil in antagonizing alcohol-heightened aggressive behavior (de Almeida et al 2004). Another β-carboline, 3-PBC, antagonized aggressive behavior at even lower doses than β-CCt.…”
Section: Discussionmentioning
confidence: 65%
“…Individual differences in the aggression-heightening effects of alcohol, another positive modulator of the GABA A receptor, are well documented (e.g., Miczek and Barry 1977;Blanchard et al 1987;Lister and Hilakivi 1988;Miczek et al 1992;van Erp and Miczek 1997;Miczek et al 1998;Fish et al 2001). Several BZs do not exert aggression-heightening effects at all: even at low doses, oxazepam, clorazepam, and zolpidem consistently produce anti-aggressive effects (Bond and Lader 1988;Martin-Lopez and Navarro 2002;de Almeida et al 2004), and triazolam fails to increase aggressive behavior in various experimental protocols (Cherek et al 1991;Kruk 1991;de Almeida et al 2004).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The α1-containing GABA A receptors seem to play a key role in mediating the pro-aggressive effect of benzodiazepines. Antagonists such as βCCt and 3-PBC that act preferentially on α1-containing GABA A receptors reduced the aggression-heightening effects of midazolam or alcohol in mice and rats (De Almeida et al, 2004; Gourley et al, 2005). In addition, 4 weeks of SI alters the expression of GABA A receptor subunits, and male mice exposed to SI showed reduced α1 subunit expression in the hippocampus and PFC compared with group housed males (Pinna et al, 2006).…”
Section: Excitatory and Inhibitory Neurotransmission And Aggressionmentioning
confidence: 99%
“…The functional importance of the α1 subunit protein for its role in aggressive behavior was investigated primarily because of the availability of α1-preferring agonists, such as zolpidem, and antagonists such as β-CCt and 3-PBC (Cox et al 1995;Huang et al 2000). Antagonist effects suggested that the α1 subunit is relevant in the aggression-heightening effects of midazolam and alcohol (de Almeida et al 2004;Gourley et al 2005). However, future studies, possibly with point-mutated animals, need to determine which subunit composition is required for flunitrazepam to heighten aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%